1951
DOI: 10.1037/h0054499
|View full text |Cite
|
Sign up to set email alerts
|

The modification of stuttering through non-reinforcement.

Abstract: "This experiment was designed under the general hypothesis that stuttering is reduced most rapidly under conditions which permit least reinforcement of the stuttering response and most reinforcement of the normal speech attempt." 20 adult stutterers served as their own controls in the experiment. "The non-reinforcement technique was held to be more effective in reducing total stuttering behavior because it substituted the normal speaking of the word for the stuttering response at the point of reinforcement." T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1961
1961
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Adaptation occurred as previously described in the literature, the greatest decrement usually occurring during the second reading, approaching an asymptote by the end of the third or fourth (Cullihan, 1963;Sheehan, 1951;Trotter, 1955). Two exceptions to this pattern occur in the base-line period for the random condition.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Adaptation occurred as previously described in the literature, the greatest decrement usually occurring during the second reading, approaching an asymptote by the end of the third or fourth (Cullihan, 1963;Sheehan, 1951;Trotter, 1955). Two exceptions to this pattern occur in the base-line period for the random condition.…”
Section: Resultssupporting
confidence: 61%
“…This result is somewhat at variance with those of other studies reported in the literature concerning both the theoretical and actual effects of punishment and reward on verbal nonfluency. These studies detail varied individual reactions depending upon both the strength and type of punishment employed and the characteristics of 5s themselves (Frick, 1951;Hill, 1954;Johnson, 1958;Shames & Sherrick, 1963;Sheehan, 1951Sheehan, , 1953Sheehan, , 1958Sheehan, Cortese, & Hadley, 1962;Sheehan & Voas, 1957;Siegel & Martin, 1965a, 1965bSkinner, 1957;Stassi, 1961;Van Riper, 1937).…”
mentioning
confidence: 99%
“…These approaches, although not strongly evidence-based, are rooted in the cognitive learning literature. [27][28][29][30] It has often been argued that evaluating such cognitive approaches is difficult because the outcomes are often challenging to quantify and the exact treatment methodologies have historically been poorly documented. Ryan 8 has asserted that for any treatment to be trusted, the treatment procedures must be adequately described so as to permit replication.…”
Section: Stuttering Management and Cognitive-restructuring Approachesmentioning
confidence: 99%
“…It should be noted that the extinction procedure employed by Yates is very similar to Dunlap's method of negative practice, in which the subject reproduces the negative behaviors voluntarily without reinforcement (Dunlap, 1932;Lehner, 1954). This method has been applied most frequently, with varying degrees of success, to the treatment of speech disorders (Fishman, 1937;Meissner, 1946;Rutherford, 1940;Sheehan, 1951;Sheehan & Voas, 1957). If the effectiveness of this psychotherapeutic technique is due primarily to extinction, as suggested by Yates' study, the usual practice of terminating a treatment session before the subject becomes fatigued (Lehner, 1954), would have the effect of reducing the rate of extinction, and may in part account for the divergent results yielded by this method.…”
Section: Counterconditioningmentioning
confidence: 99%